Mahalnya Pembiayaan di Bank Syariah - Sujian Suretno; Rivai Yusuf (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This study provides a comprehensive picture of the public's perception of the high cost of financing Islamic banks in Indonesia. The perception of